The effects of feeding low levels of concentrate to early lactating dairy cows - Llopis Palomares, Adriana (SLU/Dept. of Animal Nutrition and Management (until 231231), 2016)
Current concerns about sustainable agriculture and the needs to reduce the use of concentrates has led researchers to investigate new approaches in feeding systems for dairy cows. The beginning of lactation is a threatening episode in cow’s life. The increasing nutrient demands for milk production often overcomes their capacity to ingest enough feed to supply their nutrient demands. In addition, exist other factors besides the physical constrains that may influence intake in cattle i.e. metabolic changes, diet composition or animal characteristics. The use of concentrates, which are rich in energy, seem to be crucial to compensate the energetic deficiencies in this lactation stage. Therefore, the hypothesis of this experiment was that cows fed with low concentrate levels during the first six weeks of lactation would have higher silage intake but lower milk yield and a more negative energy balance. Thirty-one cows were used in the experiment during their first six weeks of lactation. The herd comprised cows with different lactation number and two breeds, Swedish Holstein and Swedish Red. Two diets with different amounts of concentrate and ad libitum silage were offered. The low concentrate group (LC) received 4-5Kg of concentrate depending on lactation number and the High concentrate group (HC) received 14-15Kg. The concentrate was based on by-products with the peculiarity of being rich in neutral detergent fibre (NDF) (88%DM, 179g/Kg DM CP, 67.4 g/Kg DM Fat, 328 g/Kg DM NDF, 53.6 g/Kg DM Ash, 32.5 g/Kg DM Starch and 13.2 MJ/Kg DM ME). The silage used was clover-grasssilage with low content in NDF and highly digestible (36.5% DM of fresh matter, 80% OMD, 138g/Kg DM CP, 391g/Kg DM NDF, 83g/Kg DM Ash, 11.7MJ/Kg DM ME and pH=4.3). All cow were milked twice daily in an Automatic Milking Rotary (AMR) system. Silage and concentrate intakes, milk yield, body weight (BW), and camera body condition score (BCS) were recorded on daily basis. Visual BCS and milk sampling for composition analysis were measured the second, fourth and sixth week of lactation for each cow. From the data collected, energy corrected milk (ECM) and energy balance (EB) were calculated. The effect of treatment was not significant for total dry matter intake (DMI), total metabolizable energy (ME) intake, energy corrected milk (ECM), energy balance (EB), and BCS. Silage intake was significantly higher within LC group. Effects of parity and breed were statistically significant for all the parameters measured except for the effect of breed and lactation number on energy balance. In conclusion, dairy cows fed with low concentrate diets during early lactation could compensate their energetic requirements for both body maintenance and milk production by eating more silage of high digestibility.